State arts agencies 1965-2003 : whose interests to serve? - Lowell, Julia, 1961-; RAND Enterprise Analysis; Rand Corporation; Wallace Foundation (Santa Monica, CA : RAND, 2004)
Three-quarters of all U.S. state and jurisdictional governments cut their arts budgets in fiscal year 2003, and more than one-half imposed further cuts in fiscal year 2004. In this first of a series of reports commissioned by The Wallace Foundation, the author argues that these state arts budget cuts reflect more than just a one-time response to fiscal crisis. That is, they reflect the political weakness of state arts agencies, a weakness stemming from the growing mismatch between the agencies' grant-making roles and structures and the cultural and political realities the agencies face. One promising solution may be for state arts agencies to shift their focus and funding from bolstering arts providers to serving people and communities. But before this shift can take place, some important conceptual as well as practical issues must be addressed.
"RAND Research in the Arts."
Includes bibliographical references (p. 35-40).
Also available on the internet via WWW in PDF format.
Keywords: Art commissions -- United States -- Finance; Government aid to the arts -- United States; United States -- Cultural policy